STUDENTS’ VOICE ON THE USE OF DEBATE AND ‘SEMI’ SIT-IN EXAM IN WRITING CLASS - Kurniasih, Kurniasih; Hidayanti, Ika; Widowati, Diah Retno (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
This descriptive qualitative research attempts to examine students’ attitude towards the implementation of debate activity in writing class and the implementation of ‘semi’ sit-in writing exam. In this study, the researchers used the term ‘semi’ sit-it exam to describe a condition when students have to develop the accepted writing outline into an argumentative essay in the exam day. Before writing the outline, students do debate activity to generating ideas as well as understanding the concept of argumentative essay through speaking activity. As many as 51 students of English Department, University of Islam Malang participated in this study. The data was collected through interview, and the obtained was analyzed and classified based on similar points. The result indicated that students learn new things and have better speaking skill through debate. On the other hand, few students argued that debate activity fails to assist them in writing process. Students responded differently towards the implementation of ‘semi’ sit-in writing exam. Some students stated ‘semi’ sit-in writing exam helped them write better and improve their writing speed while some students found difficulties to write essay with no help from others.